Secondary lymphoid tissue and costimulation‐blockade resistant rejection: A nonhuman primate renal transplant study. Issue 8 (12th April 2019) - Mulvihill, Michael S.; Samy, Kannan P.; Gao, Qimeng A.; Schmitz, Robin; Davis, Robert P.; Ezekian, Brian; Leopardi, Francis; Song, Mingqing; How, Tam; Williams, Kyha; Barbas, Andrew; Collins, Bradley; et al.
Abstract : Naïve T cell activation requires antigen presentation combined with costimulation through CD28, both of which optimally occur in secondary lymphoid tissues such as lymph nodes and the spleen. Belatacept impairs CD28 costimulation by binding its ligands, CD80 and CD86, and in doing so, impairs de novo alloimmune responses. However, in most patients belatacept is ineffective in preventing allograft rejection when used as a monotherapy, and adjuvant therapy is required for control of costimulation‐blockade resistant rejection (CoBRR). In rodent models, impaired access to secondary lymphoid tissues has been demonstrated to reduce alloimmune responses to vascularized allografts. Here we show that surgical maneuvers, lymphatic ligation, and splenectomy, designed to anatomically limit access to secondary lymphoid tissues, control CoBRR and facilitate belatacept monotherapy in a nonhuman primate model of kidney transplantation without adjuvant immunotherapy. We further demonstrate that animals sustained on belatacept monotherapy progressively develop an increasingly naïve T and B cell repertoire, an effect that is accelerated by splenectomy and lost at the time of belatacept withdrawal and rejection. These pilot data inform the role of secondary lymphoid tissues on the development of CoBRR and the use of costimulation molecule–focused therapies. Abstract : Introducing two surgical maneuvers—lymphatic ligation and splenectomy, designed to anatomically limit access to secondary lymphoid tissues—successfully controls costimulation blockade–resistant rejection and facilitates belatacept monotherapy in a nonhuman primate model of kidney transplantation without adjuvant immunotherapy.